2019
DOI: 10.12693/aphyspola.135.668
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Carbon Nanotube Ratio on Mechanical and Morphological Properties of A356-Carbon Nanotube Composites

Abstract: In this study, CNT-A356 composites were obtained by reinforcing an aluminium alloy A356 matrix with 4 different ratios (0.5, 1, 1.5 and 2%) of carbon nanotubes, and hardness, wear and microstructure properties of these composites were investigated. Powder metallurgy method was used for producing composites. A356 powders and CNTs were mixed via ball milling for 1 h, and cold pressed in powder pressing mold. After that, mold was taken into a functional furnace, and hot pressing operation was carried out. Pressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…εr refers to the radial deformation, ε θ refers to the tangential deformation. Strain-stress relation [12];…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…εr refers to the radial deformation, ε θ refers to the tangential deformation. Strain-stress relation [12];…”
Section: Methodsmentioning
confidence: 99%
“…Using the finite element method, it was concluded that the stress components occurring in the layers of the material are lower than those on the lower and upper surfaces, and there is an increase in the plastic stress components depending on the number of iterations [7].The behavior of composite materials against high temperatures is different from each other. In different studies, the mechanical properties and thermal behavior of different composite materials were investigated [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%